Gaul Ala Rasul: Interpretasi di Masyarakat - Sulthani, Dinil Abrar (Jurnal Penelitian Pendidikan Islam, 2020)
This article was written to explain slang for the younger generation connected with the example of the Prophet. In the perception of some people, slang has a bad connotation. This is because some of the younger generations carry out activities that are contrary to local religious and legal values. The conditions of the times have an influence on the development of the personality of the younger generation, including in their attitude and actions to be superior. This thought paper aims to discuss the activities of the younger generation, such as challenges, problems, and their potential. The writing of thoughts is described using the literature study method with a qualitative descriptive analysis approach. The results of the study show that 1) The younger generation can maximize their potential by interacting like the Prophet's example, 2) Interacting politely with their friends, and 3) The younger generation can be role models for the community. The conclusion is that the younger generation get along in the best way. In imitating the Prophet, the younger generation needs to do: 1) Starting from themselves to worship and preach, 2) Reminding and motivating each other, and 3) Doing activities as a form of love for Allah SWT.